Modeling and numerical study of actuator and sensor effects for a laminated piezoelectric plate - Costa, L. (2007)
The aim of this paper is to derive a reduced model for a piezoelectric plate and to study its actuator and sensor capabilities. In the first part, we focus on the asymptotic modeling for thin plates formed by stacking layers of different piezoelectric materials. In the asymptotic model, the mechanical and electric unknowns are shown to be partly decoupled. In the second part, we study the actuator and sensor capabilities of this model. We use two discrete non-differentiable multi-objective optimization problems, which are solved by genetic algorithms. Several numerical results are reported.